A system for evaluating big data analytics performance - Jusoh, Yusmadi Yah; Affendey, Lilly Suriani; Nor, Rozi Nor Haizan; Abdullah, Rusli; Mohamed, Ismail (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Despite of advances in systems and practices, performance measurement remains instrumental in helping organization discover existing problems and propose viable solutions. On big data Analytics (BDA), more efforts are being focused, but performance side is still a room for improvement. This paper discusses the development and implementation of performance measurement prototype system for big data systems. With this system, organizations can continually assess the performance gains and setbacks of their big data systems. The systems were developed based on measures and metrics retrieved from the extant literature. Then it was evaluated through review of subject-matter experts and usability survey. The development process of the prototype and the results of the evaluation are presented in this paper.